Current Status of Burnout in Canadian Radiology. Issue 1 (February 2023) - Cao, Daniel J.; Hurrell, Casey; Patlas, Michael N.
Burnout is a healthcare concern affecting physicians around the world. Physicians experiencing burnout tend to display signs of emotional exhaustion, depersonalization, and low personal accomplishment. Ongoing burnout trends have posed numerous challenges to Canadian physicians, notwithstanding the added complexity of the COVID-19 pandemic's impact in recent years. In particular, Canadian radiologists frequently reported experiencing high rates of burnout. This review aims to examine prominent factors affecting burnout in Canadian radiologists and summarize the impact of recent trends. In doing so, the overall wellbeing of Canadian radiologists can be assessed, and strategies for improvement can be discussed as the Canadian healthcare system prepares for new challenges of increasing demand and pressures.